A histochemical study of the asbestos body coating. Issue 2 (April 1972) - Governa, M.; Rosanda, C.
Abstract : Governa, M., and Rosanda, C. (1972). Brit. J. industr. Med., 29, 154-159. A histochemical study of the asbestos body coating. Asbestos bodies after iron extraction were tested by histochemical methods for mucopolysaccharides. The results of the reactions suggest that acid mucopolysaccharides are present in the coating of most bodies. During the formation of the bodies acid mucopolysaccharides might act as a matrix for iron deposition on the coating.